Penerapan Media Interaktif Berbasis Canva untuk Meningkatkan Maharah Al-Kalam Siswa Kelas VIII.12 MTsN 2 Makassar - Anisapitri; Wahyudin Wahyudin; Abdul Qahar Zainal; Agus Salim Beddu Malla; Subaedah Subaedah (Journal of Digital Arabic Language Education, 2026)
This study aims to improve the Maharah Al-Kalam (speaking skills) of eighth-grade students in class VIII.12 at MTsN 2 Makassar through the implementation of Canva-based interactive media.The research is motivated by the students' low speaking proficiency, as observed in pronunciation, fluency, confidence, and their ability to express ideas in Arabic, coupled with the use of conventional teaching methods. The research employed Classroom Action Research (CAR) conducted over two cycles. The subjects were students of class VIII.12 at MTsN 2 Makassar.Data collection techniques included observation, tests, and documentation. The data were analyzed descriptively using both quantitative and qualitative approaches. The results indicate that the application of Canva-based interactive media effectively improved students' Maharah Al-Kalam. Teacher activity increased from 62.5% in Cycle I to 100% in Cycle II, while student activity also rose from 62.5% to 100%. The average Maharah Al-Kalam score increased from 56 in the pre-cycle stage to 72.8 in Cycle I and 82.8 in Cycle II, with the classical learning completeness percentage reaching 90.9% in Cycle II. Therefore, it can be concluded that Canva-based interactive media is effective in enhancing students' speaking skills and creating a more engaging and interactive Arabic learning environment.